Characteristics of public workers - Lajos Tamás Szabó (Magyar Nemzeti Bank, 2022)
In our study, we set out to present the characteristics of public workers between 2011 and 2019 based on the comprehensive and anonymous administrative database of the Hungarian State Treasury (MÁK). During the years under review, altogether 676 thousand people were involved in the programme. There are great differences in terms of the total time spent in the programme individually. While the national average is more than one and a half years, it is less than one year in the more developed districts of the country and more than three years in the most disadvantaged areas. The public work programme significantly facilitated the involvement of previously inactive people in the labour market, as roughly two thirds of public workers had been inactive prior to the public work. The ratio of public workers to thepopulation is high in the districts where the ratio of those working in the primary labour market is low. Thus public work contributed to the reduction of employment disparities across the regions of the country. Chances of employment after public work increased with the passage of time, which may have been attributable to the dynamic economic growth of Hungary. While those who had been public workers in 2012 worked 15 per cent of their time in the primary labour market in the next year, in the case of those who were public workers in 2018 this ratio was close to 25 per cent. However, there are major differences between the developed and less developed areas of Hungary in terms of job finding rate as well. Public workers more often change jobs in the primary labour market, and work in a job for a shorter period of time than those who have not been public workers.
Keywords: J08; J45; J48; 330; public work programme; job finding rate; regional differences